Women at familial risk of breast cancer electing for prophylactic mastectomy: frequencies, procedures, and decision-making characteristics - Schott, Sarah; Vetter, Lisa Marie Andrea; Keller, Monika; Bruckner, Thomas; Golatta, Michael; Eismann, Sabine; Dikow, Nicola; Evers, Christina; Sohn, Christof; Heil, Jörg (Archives of gynecology and obstetrics, 2017)
Background: Some women of families at high risk of breast cancer (BC) choose prophylactic mastectomy (PM) in spite of ambiguous evidence for survival benefits. The aim of this study was to investigate counselees’ characteristics, decisions on PM, and frequencies of different procedures to better understand how to tailor interventions. Patients and methods: Eight hundred and forty-nine counselees who attended interdisciplinary consultation for genetic risk adjustment at the University Hospital Heidelberg between July 2009 and July 2011 received a tripartite questionnaire addressing sociodemographic characteristics, psychological parameters, behavioural questions, and medical data. Results: Six hundred and twelve of the 849 counselees (72%) returned the questionnaire. Four hundred were classified as high risk of genetic BC (19.5% BRCA mutation carriers; 4% unclassified variant (UV); and 76.5% calculated as high risk by pedigree). Two hundred and thirteen out of 400 (53%) were diagnosed with BC. Fourteen out of 54 (27%) BRCA mutation carriers with BC chose contralateral PM (CPM) compared to 24/126 (14%) without a mutation but with a personal BC history (p = 0.2175). Of those without BC, 12/27 (44%) mutation carriers opted for bilateral PM (BPM) compared to none without a mutation (p < 0.0001). Women who received any PM (CPM and BPM) reported a higher emotional burden from partners (p = 0.003) and family (p = 0.008), more worries regarding children and family (p = 0.003) and were associated with positive mutation status and higher heterozygous and lifetime risk (all p < 0.001). Conclusion: Although evidence on survival benefit is unclear in several clinical situations, a relevant number of counselees opt for PM. Counselees may decide based on other reasons than survival benefit.